The prevelance of mesiodens in a group of non-syndromic Turkish children: a radiographic study - Gülsüm Ak; Özen Doğan Onur; Arzu Pınar Erdem; Gamze Aren (Istanbul University, 2018)
DOI: 10.26650/eor.2018.456Purpose The aim of the present study is to determine the prevelance and clinical status of mesiodens in a group of non-syndromic Turkish children, with an analysis of the associated clinical-eruptive complications. Materials and Methods This study sample consists of 58142 pediatric patients'. Standard equipment and films were used in the suspected patients. The examination of all radiographs was performed under standard conditions by two pediatric dentists with over 10 years experience. Age, gender, number of mesiodens, morphology and clinical status were recorded in forms. Results A total of 83 mesiodentes were diagnosed in 59 children with ages ranging from 6-14 years. The prevelance of mesiodens was estimated as 0.1%. Males were more frequently affected than females in the ratio of 2.3:1. Of the 83 mesiodentes, 48.2% were conical, 31.3% were tuberculate and 20.5% were incisor like, 22.9% were inverted, and 68.7% were fully impacted. The number of mesiodens was one in 36 cases (61.0%), two in 22 cases (37.3%) and three in one case (1.7%). The mean age at the time of diagnosis of the mesiodens was 9.5 years. The main complication associated with the mesiodens was displacement or rotation of the permanent teeth (73.3%). Conclusion This study presents 0.1% prevelance of mesiodens in a group of Turkish children sample. The majority of the mesiodentes were unilateral located in the premaxillary region, were conical shaped, and remained unerupted. The mean age at the time of diagnosis of the mesiodens in this study was 9.5 years, with this period being later than the eruption time of the maxillary central incisor.